Penguatan Ketaatan Hukum Sebagai Wujud PembangunanBudaya Hukum(Pengabdian Di Desa Tuik Kecamatan Kelapa Kabupaten Bangka BaratPropinsi Kepulauan Bangka Belitung) - Reski Anwar (Wijayakusuma Law Review, 2020)
Obedience to law is one of the harmony of legal culture in community life. Legal culture can be built startingfrom the family environment and individuals belonging to the family. The purpose of community serviceactivities in the village of Tuik Kelapa district of West Bangka District is in order to build Community legalawareness. This dedication activities include legal counseling in arranging the technical guidelines ofregulations in the village, subsequent dialogue on the Justice of women and children and the assistance of legalproblems to materialize a peaceful legal culture and Orderly. The impact of this dedication activity is to developa level of legal awareness for citizens, individuals and order and to be regulated in the Association of society.Furthermore, the results of this dedication are scientific publications, growing the level of public awareness andthe formation of high concern in women and children, and understand the legal characteristics of the villageregulations.